Concepções alternativas e ensino de biologia: como utilizar estratégias diferenciadas na formação inicial de licenciados - Oliveira, Silmara Sartoreto de [UNESP] (Setor de Educação da Universidade Federal do Paraná, 2005)
The present work aimed at to diagnose how histology classes of Biological Sciences Course grow in what refers to the students' difficult learning on the scientific concept related to Muscular Tissue. To the evaluation, it was opted for the investigation of the students' alternative conceptions regarding the structure and function of the muscular fiber and for that, an interview was initiated to evaluate the learning difficulties presented by the same ones. The results of this interview guided the organization of a questionnaire to be applied to the students. The answers were appraised in the aspects regarding to the characteristics of the schemes (the students' drawings). It was concluded that the students showed difficulty in the three-dimensional vision of the cell, being difficult to associate the organelles form, location and function, that constitute the muscular fiber. Based on the obtained conclusions it was presented a teaching strategy to go to the encounter of the students' difficulties. Such strategy consisted of several stages. Initially, the professor could investigate the students' alternative conceptions on the content to be administered. In the sequence, the theoretical content would be developed, however the introduction of a problem regarding current situations, would motivate the students to transfer for this practical situation the contents supplied in the theoretical class. It would be important that the professor proposed to their students a differentiated practical activity building a model. With that it is believed that the students may solve the difficulties related to the disposition of the structures, taking advantage of the content learning, favoring teaching situations and learning based on the representation of practical situations for the student.

O presente trabalho objetivou diagnosticar como as aulas de histologia do Curso de Ciências Biológicas se desenvolvem no que se refere ao difícil aprendizado dos alunos sobre o conceito científico relacionado a Tecido Muscular. Para a avaliação, optou-se pela investigação das concepções alternativas dos alunos a respeito da estrutura e função da fibra muscular e para tanto, iniciou-se por uma entrevista para avaliar as dificuldades de aprendizagem apresentadas pelos mesmos. Os resultados desta entrevista orientaram a organização de um questionário a ser aplicado aos alunos. As respostas foram avaliadas nos aspectos referentes às características dos esquemas (desenhos dos alunos). Concluiu-se que os alunos apresentam dificuldade na visão tridimensional da célula, não conseguindo associar a forma e a localização e função das organelas que constituem a fibra muscular. Baseado nas conclusões obtidas, apresentou-se uma estratégia de ensino que fosse ao encontro das dificuldades dos alunos. Tal estratégia constou de várias etapas. Inicialmente, o professor poderia, investigar as concepções alternativas dos alunos sobre o conteúdo a ser ministrado. Na seqüência, o conteúdo teórico seria desenvolvido, porém a introdução de um problema referente a situações atuais, motivaria os alunos a transferir para esta situação prática os conteúdos ministrados na aula teórica. Seria importante que o professor propusesse aos seus alunos uma atividade prática diferenciada, construindo uma maquete. Com isso acredita-se que os alunos poderão sanar as dificuldades relacionadas à disposição das estruturas, aproveitando melhor o aprendizado do conteúdo, favorecendo situações de ensino e aprendizagem baseadas na representação de situações práticas para o aluno.
Alternative conceptions and biology teaching: how to use differentiated strategies in the initial formation of graduated
Keywords: concepções alternativas; diagnóstico; estratégias de ensino; alternative conceptions; diagnosis; teaching strategies